2013
DOI: 10.1021/np300814k
|View full text |Cite
|
Sign up to set email alerts
|

NMR Solution Structure Study of the Representative Component Hydroxysafflor Yellow A and Other Quinochalcone C-Glycosides fromCarthamus tinctorius

Abstract: Hydroxysafflor yellow A (HSYA), a representative component of Carthamus tinctorius, has attracted much attention because of its remarkable cardiovascular activities. Its structure was originally reported in 1993 and has been widely cited to date. In our experiments, its solution structure was studied using NMR techniques in different solvents, including DMSO-d(6), pyridine-d(5), and CD(3)OH. The results indicate that the structure of HSYA is different than the previously described 1b, with 3-enol-1,7-diketo fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 22 publications
0
47
0
2
Order By: Relevance
“…In addition, the correlations between OHÀ C (7) and C(4)/C(5)/C(6)/C(7)/C(8) in the HMBC spectrum suggested an intramolecular hydrogen-bond between OHÀ C(7) and the carbonyl group at C(5) position ( Figure 3). [11][12][13] Thus, the planar structure of (+)-1a was established.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the correlations between OHÀ C (7) and C(4)/C(5)/C(6)/C(7)/C(8) in the HMBC spectrum suggested an intramolecular hydrogen-bond between OHÀ C(7) and the carbonyl group at C(5) position ( Figure 3). [11][12][13] Thus, the planar structure of (+)-1a was established.…”
Section: Resultsmentioning
confidence: 98%
“…The 1 H-NMR spectrum demonstrated that the major isomer (+)-1a possessed two chelated phenolic hydroxy groups (δ(H) 17.64 (1H, s, OHÀ C(7)) and 11.69 (1H, s, OHÀ C(1'))), one olefinic group (δ(H) 7.31 (1H, d, J = 15.8, HÀ C(8)) and 7.76 (1H, d, J = 15.8, HÀ C(9))), two monosubstituted benzene ring (δ(H) 7.67 -7.17 (10H, overlap, HÀ C(11 -15), HÀ C(11' -15'))), one methoxy (δ(H) 3.84 (3H, s, HÀ C(17'))), three methyl groups (δ(H) 1.58 (3H, s, HÀ C(16)), 1.53 (3H, s, HÀ C(17)) and 1.40 (3H, s, HÀ C(18))), two methylene groups (δ(H) 3.25 (1H, d, J = 13.5, HÀ C(16'a)), 3.17 (1H, d, J = 13.5, HÀ C(16'b)), 2.82 (1H, dd, J = 17.3, 13.4, HÀ C(8'a)) and 2.29 (1H, dd, J = 17.3, 2.8, HÀ C(8'b))) and one methine group (δ(H) 4.70 (1H, dd, J = 13.4, 2.8, HÀ C(9'))). The 13 C-NMR and DEPT spectra of (+)-1a ( Table 1) exhibited 35 carbon signals including five carbonyl groups (δ(C) 209.2 (C(3)), 202.1 (C(5)), 198.2 (C(1)), 196.0 (C(7')) and 183.4 (C(7))), two monosubstituted benzene ring (δ(C) 134.8 (C(10)), 129.1 (C (12,14)), 129.0 (C(11, 15)), 131.3 (C(13)) and δ(C) 137.9 (C(10')), 129.4 (C(12', 14')), 129.1 (C(11', 15')), 126.1 (C(13'))), one hexasubstituted benzene ring (δ(C) 154.0 (C(3')), 153.5 (C(1')), 147.5 (C(5')), 129.7 (C(4')), 110.1 (C(2')) and 103.9 (C(6'))), two olefinic carbons (δ(C) 144.3 (C(9)) and 120.7 (C(8))), three quaternary carbons (δ(C) 111.0 (C(6)), 58.3 (C(2)) and 55.4 (C(4))), one oxygenated methine groups (δ(C) 80.1 (C(9'))), one methoxy (δ(C) 60.2 (C(17'))), three methyl groups (δ(C) 28.7 (C(18)), 24.3 (C(16)) and 18.4 (C(17))) and two methylene groups (δ(C) 44.1(C(8')) and 33.5 (C(16'))).…”
Section: Resultsmentioning
confidence: 99%
“…# P \ 0.01 compared with the control group (0 mg/l) active ingredient of the safflower plant (C. tinctorius L), has two solution structures of keto-enol tautomers (2a and 2b). Keto-enol tautomers 2a is the preferred tautomer with the 1-enol-3,7-diketo form (Feng et al 2013). It has been demonstrated that HSYA can antagonize platelet aggregation and inhibit thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…HSYA was isolated and purified from the aqueous extract of C. tinctorius L. by macroporous resin-gel column chromatography, as described previously (Zang et al, 2008). The molecular weight of HSYA is 612 and the molecular structure has been previously described by Feng et al (2013). HSYA was diluted with aseptic 0.9% NaCl for experimental use.…”
Section: Methodsmentioning
confidence: 99%